Kondisi Lingkungan Pekerjaan Sebagai Ukuran Kesetiaan Pada Organisasi - Sulistyan, Riza Bahtiar (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
Good working environment conditions can encourage employees from within and will increase employees' commitment to the organization. This study aims to test the model of good working environment conditions in increasing the commitment of employees to the organization, directly or indirectly through the encouragement that is in the employees. There are 41 employees willing to be respondents. The analysis method used is Partial Least Square (PLS). The results show that good working environment conditions can encourage employees from within themselves will increase the commitment of employees to the organization. The most important thing is to pay attention to the inner drive to keep high employee commitments.